SISTEM PAKAR DIAGNOSIS GANGGUAN KEHAMILAN MENGGUNAKAN METODE FORWARD CHAINING (STUDI KASUS : RUMAH SAKIT KAMBANG) - Lisdarti (JURNAL AKADEMIKA)
Pregnancy is something that is very important for a mother. Information about pregnancy disorders that occur during pregnancy is needed, especially for pregnant women. Pregnant women tend to feel symptoms that are different from the normal pregnancy experienced by pregnant women. The risk of maternal mortality is caused by several factors, namely being late to recognize danger, delaying decision making to be referred, being late to health facilities and being late to get adequate services by health workers. The purpose of this study is to design an expert system for pregnancy disorders by applying the Forward Method Chaining. The system to be designed is a system that transfers the knowledge of a doctor to an expert system (Artificial Intelligence), which will help patients know the disease they are suffering from. This system is designed based on Website using PHP Framework Code Igniter script and using MySQL database. With the established Pregnancy Disorders Expert System, it makes it easier for pregnant women to diagnose pregnancy disorders so that they can provide the right treatment or treatment.